Mecânica quântica em cavidades de microondas - Sheilla de Oliveira Marques (2016)
In our work, we studied the foundations of quantum mechanics in microwave quantum cavities using some of the experiments Serge Haroche and his team performed. We started by reviewing the basic concepts of quantum mechanics, and then we described the central concept behind the experiments, the quantum cavity electrodynamics. We studied the quantization of the electromagnetic field and coherent states, and from the Jaynes-Cumming model, where we described the atom-field interaction dynamics. We studied the light quantizations through the experiment described in Ref. [M Brune et al., Physical Review Letters, 76(11):1800, 1996]. Another fundamental concept of quantum mechanics, entanglement, was studied using Ref. [E Hagley et al. Physical Review Letters, 79(1):1, 1997]. Finally, we studied decoherence and classical limit through the experiments in Ref. [Michel Brune et al Physical Review Letters, 77(24):4887, 1996] e [P Bertet et al., Nature, 411(6834):166–170, 2001.].